Improved power quality buck boost converter for SMPS - J. Jayachandran; S. Malathi (Institute of Advanced Engineering and Science, 2019)
In this paper, a Neural Network (NN) controlled Buck-Boost Converter (BBC) based Switched Mode Power Supply (SMPS) for a PC application is proposed. The proposed BBC is analyzed, modeled and designed for the rated load. Generally, the utilization of Multiple Output SMPS (MOSMPS) for PC application introduces Power Quality (PQ) issues in the power system network. Unlike conventional SMPS the proposed NN controlled BBC can accomplish improvement of power quality. The NN controller reduces the Total Harmonic Distortion (THD) of source current below 5%, maintains input side Power Factor (PF) to be nearly unity and improves the output voltage regulation. In the proposed system, NN controller replaces the conventional PI controller and overcomes the drawbacks of the conventional system. The proposed BBC is validated adopting MATLAB/SIMULINK software. The simulation analysis validate that the proposed NN controlled BBC performs better than conventional converter in terms of PQ indices under fluctuating conditions.